Avaliação dos parques urbanos de Fortaleza/CE: uma proposta de ferramenta para auditoria - Saraiva, Marianna de Andrade (2020)
Parks usually have two main objectives in urban centers: to provide ecosystem services to the population that lives in their surroundings and to preserve the natural environment, promoting quality of life and environmental balance in cities. Planning and management of urban green space require a variety of information that enables assessments and diagnostics in order to assist in the decision making process. This article aims to evaluate the urban parks located in the city of Fortaleza, Ceará, based on the construction of an audit tool. Among the possible ways of applying an auditing, the in situ observation assisted by paper forms was chosen, due to three aspects: the ease in its use, the amount of resources available and the safety of the observer. In order to identify the relevant indicators, a bibliographic and documentary research was done to obtain the initial set of indicators of the proposed system. The tool was divided into two dimensions: environmental conservation and public use because, ideally, the parks should maintain these two functions simultaneously and in a balanced way. There are 18 urban parks under municipal administration in Fortaleza. Each one of them has been evaluated once by 2 evaluators simultaneously and consensually, on working days during daylight, trying to follow similar and replicable conditions in future assessments made by the managers of the parks, if they choose to continue the assessment with the proposed tool. It has been proposed the modelling of an index capable of expressing quantitatively the condition of the park in the evaluated dimensions with the purpose of making a more objective analysis and the managers’ decision making process easier. The mentioned index was named Urban Park Condition Index (UPCI). The results of the assessment made it clear that most of the urban parks in Fortaleza have weaknesses in both evaluated dimensions, generating a low value for the UPCI. The variables that contributed the most for this outcome were: parking lot, bicycle paths network, bike racks, bathrooms and signaling. More than 70% of the evaluated parks did not have all of these structures, what can be considered vulnerable points in these spaces. The park that presented the best outcome was the Urbano da Liberdade Park and the one that presented the worst outcome was the Presidente Geisel Grove. It is intended that the proposed instrument will become an observation tool for the evaluation and monitoring of urban parks located in Fortaleza, Ceará, therefore, the observations of this research would contribute as an initial database and as a reference for future evaluations.